Trascendentalismo, contenido semático y verdad - Barrio, Eduardo A. (Análisis Filosófico, 1996)
In his article "The Status of Content", Boghossian defends what has been called "trascendentalism about content". According to him, the thesis that there is nothing in the world that corresponds to our thoughts "is not merely implausible but incoherent’’. In other words, he thinks that the thesis in question is not simply false on empirical basis but rather self-refuting or pragmatically incoherent. My purpose in this article is to show that Boghossian’s argument for his point ofview is not valid. My main thesis is that there is no contradiction in applying the notion oftruth to both semantical and psychological sentences and, al the same time, holding that there are neither semantic nor mental contents.